MINERALOGY AND CHROMIUM, NICKEL, COPPER, ZINC AND LEAD CONTENTS AROUND CAXIMBA LANDFILL IN CURITIBA-PR - ZANELLO, Sonia; MELO, Vander de Freitas; WOWK, Gisele Inês Taraszkiewecz Harbar (Scientia Agraria, 2009)
Seven soil profiles were collected around Caximba Landfill, in Curitiba – PR, to characterize and quantify clay fraction mineral and to determine total and exchangeable Cr, Ni, Cu, Zn and Pb contents. Clay Fraction was studied by x-ray diffractometry (XRD), thermal analysis and chemical extractions with ammonium oxalate (AO) and sodium dithionite-citrate-bicarbonate (DCB). Heavy metals total and exchangeable contents were determined by atomic absorption spectrophotometry, after sample acid digestion (H2SO4, HF, HNO3 e HClO4 concentrated) and extraction with BaCl2 1 mol dm-3, respectively. The predominance of kaolinite, which varied between 548,5 to 702,1 g kg-1, and the occurrence of vermiculite with hidroxi between layers in clay fraction, determined the soils relatively high CEC. Iron oxide contents were low, making the nature of the parent material evident (granite/gneiss and clay-silt sediments) and the Fe reduction conditions and removal to soils under hydromorphism influence. In a general way, increase of heavy metals contents around Caximba Landfill soil was observed. Although, contamination levels were not very expressive, related to the low concentrations of Cr, Ni, Cu, Zn and Pb in leachate; leaching facility in hydromorphic soils; high divalent and trivalent cation contents (Ca2+, Mg2+ e Al+3) in sorptive soil complexes.